Efficiency Of Physicochemical Methods In Assessing The Quality Of Canned Products (Progress Annals: Journal of Progressive Research, 2025)
This article explores the effectiveness of physicochemical methods in evaluating the quality of canned food products. In the context of growing food safety requirements and increasing consumer demands, precise and reliable assessment techniques are essential. The study focuses on determining key parameters such as pH level, total soluble solids (TSS), titratable acidity, and the presence of preservatives or contaminants. By comparing traditional sensory analysis with instrumental physicochemical techniques, the research highlights the advantages of modern laboratory diagnostics in ensuring the stability, nutritional value, and compliance of canned goods with regulatory standards. The results demonstrate that physicochemical approaches offer higher objectivity, reproducibility, and sensitivity in quality assessment processes